Pengaruh Tingkat Efektivitas Iklan Youtube Pantene Miracles Hair Terhadap Minat Beli Pada Masyarakat Kabupaten Bekasi - Trimanah Trimanah; Urip Mulyadi; Absara Lita (Brand Communication, 2022)
On January 2, 2022 Brand Pantene introduced its newest product, Miracles Hair Supplement, which was then followed by the release of an advertising campaign titled bye #rambutcapek hello #rambutcharged. The campaign put Keanu Agl, a celebgram with long hair, as the star of the ad. The number of views for the ad on Youtube has reached more than 45 million and with more than 182 thousand positive comments. This study aims to determine the effect of Pantene Miracles Hair Supplement #RambutCapek #RambutKeCharged advertising on purchase intention, using four variable dimensions, there are Empathy, Persuasion, Impact, and Communication (EPIC). This is a quantitative research with data collection techniques using questionnaires distributed to 100 respondents obtained through purposive sampling technique. The theory used is the theory of selective influenza. The results showed that this Pantene Youtube Ad proved effective in influencing buying interest with each dimension getting a score of 4.04 (Empathy), 3.86 (Persuasion), 4.02 (Impact), 4.07 (Communication) and with an average score of 3.98. This ad has not been able to achieve a maximum score of 5 due to the selectivity of consumers in determining their interest in the advertised product.